PENGARUH CORPORATE GOVERNANCE DAN MANAGEMEN LABA TERHADAP PENGUNGKAPAN LAPORAN KEUANGAN - IRWANTO HANDOJO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
Disclosure of financial statements is an important factor in achieving the efficiency of capital markets and a means of public accountability. The purpose of the study was to get empirical study about the influence of corporate governance and earnings management on the disclosure of financial statements. Samples are 41 companies listed in Indonesia Stock Exchange tested using multiple regression analysis. The results of the study provide evidence that corporate governance can drive more disclosure of financial statements information. This is evidenced by the influence of public ownership and the board of directors on the disclosure of financial statements.